BALATINDAK AND BASALENDENG: HISTORICAL STUDIES IN BANGGAI ISLANDS REGENCY - Koano, Dion Marselo; Mondong, Tonny Iskandar; Tasnur, Irvan (Satmata: Journal of Historical Education Studies, 2025)
Balatindak and Basalendeng are traditional forms of performing arts or dances that are often presented during welcoming ceremonies for distinguished guests, weddings, and cultural art events. This study aims to explore the historical background of the Balatindak and Basalendeng dances in Banggai Kepulauan Regency, as well as to examine their current existence. The research employs a qualitative method with a descriptive approach to describe the history and current relevance of the Balatindak and Basalendeng dances in the region. Data collection was conducted through observation, interviews, and documentation. The results indicate that the Balatindak and Basalendeng dances have deep historical roots, closely tied to the culture of the Sea-Sea ethnic group in Banggai Kepulauan, dating back to the 7th century. Originally, these dances served ritualistic and sacred purposes within the belief systems and customs of the Banggai Kingdom. However, major transformations began during the Dutch colonial period in the 19th century, shifting the dances from sacred rituals to cultural performances. Today, these dances face increasing threats. The younger generation is showing a declining interest, resulting in a lack of regeneration that endangers the continuity of this cultural heritage. Changing lifestyles, limited documentation, and the absence of integration into the education system present additional challenges. Nevertheless, Balatindak and Basalendeng still have the potential to be preserved. Collaborative efforts among indigenous communities, local governments, and educational institutions are essential in transforming preservation strategies through educational approaches, digital archiving, and the use of social media as a platform for cultural promotion.